Case series on placenta accreta spectrum disorder and its management - Kumari, Maya; Patel, Amrita D.; Mashruwala, Vishrut (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Placenta accreta spectrum (PAS) is a potentially life-threatening obstetric condition that requires a multidisciplinary approach to management. The main complication of PAS is due to it’s massive obstetric haemorrhage which leads to maternal morbidity and mortality. The incidence of placenta accreta spectrum increases day by day due to an alarming increase in caesarean section rates. Depending on the range of invasiveness, The Placenta accreta spectrum is classified as placenta accreta, placenta increta and placenta percreta. We report here a series of 5 cases of placenta accreta spectrum and their management at our centre. With all due pre-op preparedness and anticipation of complications. All 5 cases had good maternal and fetal outcome. In 3 cases hysterectomy was required and 2 cases uterus could be preserved.